2016
DOI: 10.1176/appi.ps.201500183
|View full text |Cite
|
Sign up to set email alerts
|

Association of Supported Employment With Cognitive Functioning and Employment Outcomes

Abstract: Results of this study imply that training in verbal learning should be included in supported employment programs. More generally, elaborated models are needed to explain interactions between cognitive functioning, supported employment, and employment outcomes and to enhance understanding of the interrelationships between cognitive functioning, employment outcomes, and any mediating and moderating variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 10 publications
(9 reference statements)
0
24
0
Order By: Relevance
“…For example, a recent multi-site study in Switzerland in participants with psychiatric illness receiving supported employment found that verbal learning was the sole cognitive predictor of job attainment and retention at 3 months. 12 In another study of a schizophrenia sample receiving supported employment, verbal learning, and executive functions were the strongest cognitive predictors of work. 5,6 Why verbal learning is such an important predictor of work is unclear.…”
Section: Discussionmentioning
confidence: 97%
“…For example, a recent multi-site study in Switzerland in participants with psychiatric illness receiving supported employment found that verbal learning was the sole cognitive predictor of job attainment and retention at 3 months. 12 In another study of a schizophrenia sample receiving supported employment, verbal learning, and executive functions were the strongest cognitive predictors of work. 5,6 Why verbal learning is such an important predictor of work is unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research from developed countries ( Landolt et al, 2016 ; McGurk and Meltzer, 2000 ; McGurk and Mueser, 2004 ), and one study from India ( Srinivasan and Tirupati, 2005 ) have found cognitive functioning is related to work in schizophrenia. The present study adds to this research by showing that cognitive functioning at baseline was significantly related to current work status in both younger and older participants.…”
Section: Discussionmentioning
confidence: 94%
“…All eight reports were original research articles published in peer-reviewed psychiatric and mental health (46)(47)(48)(49)(50)(51), or neuropsychological (52) journals, including one brief report (47). Table 1 describes the included research articles in terms of publication year, country in which the sample was recruited, total analyzed sample size, target group, and vocational intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Of eight articles included, seven found a significant predictive effect of any neuropsychological measure in multivariate models predicting work outcomes of the vocational rehabilitation program (46)(47)(48)(49)(50)(51)(52). Considering that some articles relied on the same samples, this implies that four out of five studies showed that higher baseline neuropsychological test scores predicted better outcomes of SE interventions.…”
Section: Results At Multivariate Levelmentioning
confidence: 99%